Perinatal depression: prevalence, outcomes and screening tools - a review of the literature - Cesa Septiana Pratiwi; Pauline Glover (Journal of Health Technology Assessment in Midwifery, 2019)
Perinatal depression (PD) is a depressive disorder in women that occurs either during pregnancy and/ or within 12 months after delivery. PD has adverse outcomes not only for mothers, but also for their children and their family/husband. A review of literature was conducted to present a comprehensive review of the available research into depression, its prevalence, risk factors and the screening tools in the context of the perinatal period. The literature will provide the background for understanding perinatal depression and will support the need for the most appropriate perinatal mental health screening-tool, particularly depression in midwifery care.